(3JNejS GdHQOIs - (3eMeO Hf SYjO Hf MeGO Hf YHO Gddg GdUfgGLj GdHhUjQj GdeUQj, TQa GdOjf, CHh YHO Gddg , (B696 (3g` s
(3ChdgG (B:s
(3GdchGcH GdOQjI ai eOM NjQ GdHQjI eG HGd Yjfjc JTch TOI GdCde QeOGA fGeJ Yjhf hgj Jfe JfOQi OeGhO ehYG ai OLi GdXde Cef JPcQ LjQGf HPi Sde s
(3BNQgG (B:s
(3jG QH hGNJe dfG HGdNjQ hGdSYO HMQeI GdOjf hGdbQBf hGdYde HLGg NjQ GdhQi Cbhi hSGFdfG hLGg cd fHi Ke cd hdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B285(3C (B- (3U(B299(3Cs
(3GfXQgG eY HZjI GdCed ai JQJjH GdcGeds
(3ddeHQOs
(3HRjGOI SHYI CHjGJ Yf GdfSNI GdChdis
(3fSNI QGHYI cGdSGHbI s
(3hHYOgG JbjjOGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs